MAKNA SIMBOL TOR-TOR ILAH MARDOGEI PADA MASYARAKAT SIMALUNGUN - SEFRINA WAHYUNI (Gesture: Jurnal Seni Tari, 2014)
Tor-tor Ilah Mardogi is showed in Rondang Bintang event. Tor-tor Ilah Mardogei tells about an activity of Simalungun Society during harvest season. Tor-tor Ilah Mardogi is escourted in poem or musical intruments as a tempo of Tor-tor movements by the dancers. The teories that is uses in the result of the research and also the supporting theory related to the topic are the theory of meaning, theory symbol, the meaning of symbol, theory of dancing and the meaning of Tor-tor. The research discuss about the meaning of symbolin Tor-tor Ilah Mardogei in Simalungun Society was conducted for 2 months, from December 2014 until Febuary 2015. The location of the research is Huta III Silau Malela village, Gunung Malela district, Simalungun regency. The population in this reearch is culture leaders, Simalungun artists, and villagers. The sample is two Simalungun artists and two traditional leaders who know and understand as well as involved in Tor-tor Ilah Mandogei. The techniques of collecting data are literature studies, interviews, observation, and documentation, which is then analyzed by qualitative descriptive method. The conclusion of this research shows up with Tor-tor Ilah Mardogei has 5 movements which are manabi omei, manjamur omei, mangipas and mamurpur omei and manunjung omei. Tor-tor Ilah mardogei has the mimetical and metaphorical meaning. It was represented farming activities in Simalungun society in the harvest seasons. It also has symbol that can be seen from its movements, music, and also the clothing. Keywords: Tor-tor Ilah Mardogei,  form, Symbol Meaning